2008
DOI: 10.1007/s10620-008-0598-y
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Pentadecapeptide BPC 157 and Short Bowel Syndrome in Rats

Abstract: The gastric pentadecapeptide BPC 157, which was shown to be safe as an antiulcer peptide in trials for inflammatory bowel disease (PL14736, Pliva), successfully healed intestinal anastomosis and fistula in rat. Therefore, we studied for 4 weeks rats with escalating short bowel syndrome and progressive weight loss after small bowel resection from fourth ileal artery cranially of ileocecal valve to 5 cm beneath pylorus. BPC 157 (10 microg/kg or 10 ng/kg) was given perorally, in drinking water (12 ml/rat/day) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(63 citation statements)
references
References 56 publications
(323 reference statements)
1
61
0
Order By: Relevance
“…A well-balanced effect that affects all of the organs equally may define the same effective counteracting dosage range for all combined organs, including the stomach, intestine, liver and brain lesions in the present study. In particular, due to the gastrointestinal (Sikiric et al 2010(Sikiric et al , 1996(Sikiric et al , 1997a(Sikiric et al ,b, 2001Klicek et al 2008;Skorjanec et al 2009;Sever et al 2009;Prkacin et al 2001a), liver (Ilic et al 2010(Ilic et al , 2009Sikiric et al 1993b;Prkacin et al 2001b) and brain (Blagaic et al 2004;Boban Blagaic et al 2005;Tohyama et al 2004;Jelovac et al 1998Jelovac et al , 1999Sikiric et al 1999;Tudor et al 2010) injuries as well as due to the gastric-liver-brain triad lesions after insulin overdose, the breakdown of liver glycogen occurs with profound hypoglycemia (Ilic et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A well-balanced effect that affects all of the organs equally may define the same effective counteracting dosage range for all combined organs, including the stomach, intestine, liver and brain lesions in the present study. In particular, due to the gastrointestinal (Sikiric et al 2010(Sikiric et al , 1996(Sikiric et al , 1997a(Sikiric et al ,b, 2001Klicek et al 2008;Skorjanec et al 2009;Sever et al 2009;Prkacin et al 2001a), liver (Ilic et al 2010(Ilic et al , 2009Sikiric et al 1993b;Prkacin et al 2001b) and brain (Blagaic et al 2004;Boban Blagaic et al 2005;Tohyama et al 2004;Jelovac et al 1998Jelovac et al , 1999Sikiric et al 1999;Tudor et al 2010) injuries as well as due to the gastric-liver-brain triad lesions after insulin overdose, the breakdown of liver glycogen occurs with profound hypoglycemia (Ilic et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…BPC 157 has been shown to counteract the liver changes induced by chronic ethanol administration (Prkacin et al 2001b), portal hypertension (Prkacin et al 2001b) and gastric lesions (Ilic et al 2009;Prkacin et al 2001a). BC157 also has been shown to reduce damage to the duodenum and colon induced by cysteamine administration (Sikiric et al 2010(Sikiric et al , 2001, and it has been demonstrated to have a prominent angiogenic effect during the healing of different types of tissues (Sikiric et al 2010(Sikiric et al , 2003(Sikiric et al , 2003Klicek et al 2008;Skorjanec et al 2009;Sever et al 2009;Tkalcevic et al 2007;Krivic et al 2006;Novinscak et al 2008;Cerovecki et al 2010). In addition, besides stimulating the expression of the egr-1 gene, BPC 157 has been shown to stimulate the expression of the egr-1 repressor nerve growth factor 1-A binding protein-2 (nab2) (Tkalcevic et al 2007).…”
Section: Route Of Medication Medicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing that pentadecapeptide BPC 157 was so far tested only in inflammatory bowel disease patients [1][2][3][4][5][6], the BPC 157 intestinal protection [i.e., 16,31,33,[35][36][37][38][39], Table 5, may be particularly interesting.…”
Section: Intestinementioning
confidence: 99%
“…Likewise, BPC 157 was shown to be highly effective in counteracting severe inflammatory bowel disease complications [37][38][39], efficacious in healing of the intestinal anastomosis [37,39,60], colon-colon [61], ileo-ileal [37] and jejuno-ileal termino-terminal anastomosis [39]. BPC 157 increases adaptative capability of the remaining intestine in all intestinal layers, fully reverses short-bowel syndrome in rats after massive intestine resection, reduces body weight loss postoperatively, induces consistent body weight gain and finally reaches the weight increase of rats with intact intestine [39]. Most importantly, providing all these findings together, the prominent healing effect of BPC 157 regimens in colocutaneous fistulas shown to be NO-system dependent [38], may also be likely valid in colocutaneous healing patients.…”
Section: Intestinementioning
confidence: 99%